Le boeuf du Lac Tchad - Malbrant, R.; Receveur, P.; Sabin, R. (1947)
The Kuri cattle breeds of Lake Chad were investigated. Descriptions of rearing environment, animal morphology and breed improvement included. Data on body measurements of oxen, cows and bulls included with discussions of their exploitation, protection, improvement, selection and multiplication.